Evaluation of Momordica balsamina and Momordica foetida from Swaziland for their antimicrobial activity, anti-proliferative properties and biochemical composition - Nkambule, Thabile (2017)
Momordica balsamina (inkakha) and M. foetida (inshubaba) are used in several countries, including Swaziland, both for food and as a traditional medicine to treat and cure several diseases. Systematically investigating their bioactivities and identifying the compounds responsible for the curative properties could greatly extend the therapeutic applications of these plant species. The aim of the present study was to investigate antimicrobial, anti-proliferative activities and biochemical composition of extracts of Momordica plants. Methanol-water extracts of M. balsamina and M. foetida leaf, stem and fruit were screened for antimicrobial activity against a range of bacteria. Gram-positive bacteria were found to be the most sensitive to Momordica extracts particularly leaf extracts. The lowest minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were from leaf extracts of M. balsamina and MBC was determined to be 2.5 mg/mL against L. monocytogenes. Following fractionation of Momordica extracts using solid phase extraction (SPE) the methanol eluted fraction showed antimicrobial activity against L. monocytogenes and S. aureus strains which was comparable to the antimicrobial activity of crude extracts. The anti-proliferative activity of methanol-water extracts, of M. balsamina and M. foetida leaf, was tested against human liver hepatocellular carcinoma (HepG2) cells. Leaf extracts from both M. balsamina and M. foetida displayed anti-proliferative activity at concentrations of 0.25 and 1mg/mL, respectively. Biochemical analysis of the extracts was carried out through Fourier transform infrared spectroscopy, high performance liquid chromatography, nuclear magnetic resonance and liquid chromatography-mass spectrometry analysis. This study demonstrated the highest total phenolic content in leaf extracts with a range of 34.39 to 47.94 mg GAE/g, followed by stem extracts with a range of 21.02 to 26.19 mg GAE/g and least by fruit extracts with a range of 3.97 to 12.97 mg GAE/g. A good correlation was revealed between the antimicrobial activity of Momordica extracts and total phenolic content suggesting that phenolic content could be partly responsible for the antimicrobial activity of the extracts, but this remains to be confirmed. These results could indicate the potential use of Momordica plants as antimicrobial agents as well as anti-cancer agents and also provide the basis for the isolation and identification of the biologically active substances in these extracts.